MANAJEMEN STRATEGIS ORGANISASI NON POLITIK DALAM LEMBAGA PENDIDIKAN ISLAM - Wasito (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2023)
This article discusses to analyze the management strategies applied by non-profit organizations in the form of institutions that are active in the field of Islamic education in Indonesia. Islamic educational institutions in Islamic boarding schools provide a greater challenge than institutions that work, Islamic educational institutions must implement strategies, tips to achieve the desired goals, quality. Islamic educational institutions are no longer considered as institutions that exist in the second class, which is considered insufficient and able to meet the needs of the community for quality education. To analyze used library techniques. In Indonesia as a non-profit organization, and has many complex challenges